2017
DOI: 10.1039/c7ra04883a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical hydrogenated TiO2nanotube arrays decorated with 3D cotton-like porous MnO2enables superior supercapacitive performance

Abstract: Highly conducting TiO2 nanotube arrays (EH-TNTAs) decorated with unique 3D cotton-like porous MnO2 enables superior supercapacitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For instance, Zhang et al [19] demonstrated that electrochemical hydrogenated TNTAs photoelectrode showed remarkably improved and stable water splitting performance, and the optimized saturation photocurrent density and photoconversion efficiency under AM 1.5G illumination were identified to be 2.8 mA cm À2 at 1.23 V vs. RHE (RHE, reversible hydrogen electrode) and 1.27% respectively. Our previous work [22] proved that in contrast to the pristine TNTAs, EH process considerably enhanced the electrical properties and electrochemical performance of TNTAs, which enabled EH-TNTAs to serve as an ideal current collector for constructing TNTA-based electrodes applied for high performance supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al [19] demonstrated that electrochemical hydrogenated TNTAs photoelectrode showed remarkably improved and stable water splitting performance, and the optimized saturation photocurrent density and photoconversion efficiency under AM 1.5G illumination were identified to be 2.8 mA cm À2 at 1.23 V vs. RHE (RHE, reversible hydrogen electrode) and 1.27% respectively. Our previous work [22] proved that in contrast to the pristine TNTAs, EH process considerably enhanced the electrical properties and electrochemical performance of TNTAs, which enabled EH-TNTAs to serve as an ideal current collector for constructing TNTA-based electrodes applied for high performance supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of TNTAs has been demonstrated to be a quite effective strategy for signicantly improving the electrical conductivity and electrochemical properties of TNTAs owing to the intentionally introduced Ti 3+ (O-vacancies) during hydrogenation process. As reported, there are many approaches for hydrogenation of TNTAs such as hydrogen thermal treatment, 17,18 hydrogen plasma treatment, 19,20 electrochemical hydrogenation (EH), 21,22 and chemical hydrogenation. 23,24 Among them, EH is a facile, low-cost and environment-friendly method, overcoming the weaknesses of other hydrogenation techniques such as expensive facility, high-energy consumption and complex process.…”
Section: Introductionmentioning
confidence: 99%
“… 19–22 Therefore, TiO 2 nanotubes need to be modified urgently in order to meet the demands for supercapacitors with high electrochemical performance. A promising method to further enhance the capacitance of TNTs is to incorporate with some transition metal oxides (NiO, 23 MnO 2 ( ref. 24 and 25 ) and MoO 3 ( ref.…”
Section: Introductionmentioning
confidence: 99%